2019
DOI: 10.3390/ma12203278
|View full text |Cite
|
Sign up to set email alerts
|

Organic Solvent-Free Olefins and Alcohols (ep)oxidation Using Recoverable Catalysts Based on [PM12O40]3− (M = Mo or W) Ionically Grafted on Amino Functionalized Silica Nanobeads

Abstract: Catalyzed organic solvent-free (ep)oxidation were achieved using H3PM12O40 (M = Mo or W) complexes ionically grafted on APTES-functionalized nano-silica beads obtained from straightforward method (APTES = aminopropyltriethoxysilane). Those catalysts have been extensively analyzed through morphological studies (Dynamic Light Scattering (DLS), TEM) and several spectroscopic qualitative (IR, multinuclear solid-state NMR) and quantitative (1H and 31P solution NMR) methods. Interesting catalytic results were obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 108 publications
0
10
0
2
Order By: Relevance
“…Therefore, a great number of oxidizing W-H 2 O 2 systems were developed to perform green oxidation reactions. So, numerous valuable oxidation processes such as alcohol, sulfide and amine oxidation and alkene epoxidation rely on tungsten-based catalysts heavily 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a great number of oxidizing W-H 2 O 2 systems were developed to perform green oxidation reactions. So, numerous valuable oxidation processes such as alcohol, sulfide and amine oxidation and alkene epoxidation rely on tungsten-based catalysts heavily 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Using several techniques, it is possible to calculate the function coverage on silica cores, an important parameter within the catalytic part. The parameter μ(f), defined in the number of groups per nm 2 , could be determined by Equation (3) [ 23 , 40 ]. The ρ’(f) parameter does correspond to the functions grafted on a silica core ( Figure 12 and Equation (2)) and is calculated from ρ(f).…”
Section: Resultsmentioning
confidence: 99%
“…The use of chlorinated solvents such as dichloroethane (DCE), a highly toxic solvent, has to be avoided [ 15 ]. In the research group, the processes have been found to be active without organic solvent using complexes with tridentate ligands [ 16 , 17 , 18 , 19 , 20 ] or polyoxometalates (POMs) [ 21 , 22 , 23 ], giving a first step towards a cleaner process. The oxidant used in this case is tert -butyl hydroperoxide (TBHP) in aqueous solution.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, in pursue of a green chemistry approach, 13–15 great changes have been introduced to develop a greener and more environmentally friendly oxidation protocols with the use of oxidants such as TBHP, 16,17 H 2 O 2 , 18 dioxygen, 19 and so on. On another hand, solvent free or aqueous solvents are preferred prevailing against the traditional solvent conditions, resulting in safer, environmentally friendlier, easy‐to‐handle, and generally improved techniques.…”
Section: Introductionmentioning
confidence: 99%